Lithiophilic N-doped carbon bowls induced Li deposition in layered graphene film for advanced lithium metal batteries - Feng, Xiaoyu; Wu, Hong-Hui; Gao, Biao; Świętosławski, Michał; He, Xin; Zhang, Qiaobao (Nano research, 2022)
Lithium (Li) metal with high theoretical capacity and low electrochemical potential is the most ideal anode for next-generation high-energy batteries. However, the practical implementation of Li anode has been hindered by dendritic growth and volume expansion during cycling, which results in low Coulombic efficiency (CE), short lifespan, and safety hazards. Here, we report a highly stable and dendrite-free Li metal anode by utilizing N-doped hollow porous bowl-like hard carbon/reduced graphene nanosheets (CB@rGO) hybrids as three-dimensional (3D) conductive and lithiophilic scaffold host. The lithiophilic carbon bowl (CB) mainly works as excellent guides during the Li plating process, whereas the rGO layer with high conductivity and mechanical stability maintains the integrity of the composite by confining the volume change in long-range order during cycling. Moreover, the local current density can be reduced due to the 3D conductive framework. Therefore, CB@rGO presents a low lithium metal nucleation overpotential of 18 mV, high CE of 98%, and stable cycling without obvious voltage fluctuation for over 600 cycles at a current density of 1 mA·cm −2 . Our study not only provides a good CB@rGO host and pre-Lithiated CB@rGO composite anode electrode, but also brings a new strategy of designing 3D electrodes for those active materials suffering from severe volume expansion.